Organizational and Social Factor Analysis: The Role of Human Resources in the Success of Information Security Systems in the Digital Business Context - Sunarso, Budi (PT. LITERASI SAINS NUSANTARA, 2024)
In the continually evolving digital business era, information security has become paramount for organizations to ensure the continuity of their operations. Information security systems involve not only technology but also organizational and social factors that play a crucial role in managing human resources. This research aims to conduct an in-depth analysis of how human resources can influence the success of information security systems in the context of digital business. The research method employed in this study is a qualitative literature review with data collection from Google Scholar for the years 2006-2024. The study findings indicate that in the ever-evolving digital era, information security is crucial in the context of digital business. Information security systems rely not only on technology but also on organizational, social, and human factors. Effective integration of technology, organization, and human resources is key to creating a strong and adaptive information security environment.